Examining a novel performance validity task for the detection of feigned attentional problems. - Morey, Leslie C. (Applied Neuropsychology: Adult)
Attention Deficit Hyperactivity Disorder (ADHD) is a diagnosis of particular significance for college students, as when present it can significantly compromise academic achievement. However, because high-stakes decisions may be riding on the outcome of an ADHD evaluation (such as access to educational accommodations or stimulant medication), the diagnosis is vulnerable to exaggeration or feigning of symptoms or impairment. This study evaluates a novel procedure, the Tests of Attentional Distraction (TOAD), which is a computer-based performance validity measure involving a low difficulty continuous performance task that directly and obviously targets attentional function. A group of college student simulators (n = 115) feigning ADHD were compared to 32 individuals diagnosed with ADHD and 221 control participants on the TOAD, as well as on symptom validity indicators from the Personality Assessment Inventory (PAI). Moderate to large effects differentiating the feigning group from control participants, both ADHD and non-ADHD, were observed for both the TOAD and PAI indicators. Incremental validity analyses indicated that the two approaches to validity assessment contributed independently to the detection of suspect responding.